Effects of fertilizer and hot water treatment upon establishment, survival and yield of plantain (Musa spp., AAB, French) - Hauser, S. (Elsevier, 2000)
Plantain (Musa spp. AAB, French, cv. Essong) was grown on an acid ultisol in southern Cameroon to determine yield response to (1) a hot-water treatment to control nematodes and (2) the application of fertilizer. Observations were made for 42 months. Establishment was unaffected by hot-water treatment or fertilizer. Hot-water treatment reduced nematode infestation to about 30% of that found in untreated plants and increased rhizome survival by 11%. Fertilizer application increased the proportion of bunch-producing plants from 44 to 65% through reduced die-back, toppling and pseudostem breakage during the dry season but had no effect on bunch weight per plant. Fresh bunch yield of the plant-crop was 10.2 Mg ha−1 in unfertilized, untreated, plots; fertilized plots produced 15.3 Mg ha−1 and hot-water treated plots 13 Mg ha−1. Fertilized and hot-water treated plots produced 20.8 Mg ha−1. First ratoon yields were unaffected by fertilizer, but increased due to hot-water treatment from 0.81 to 5.0 Mg ha−1. Plant-crop bunch weight decreased with increasing time between planting and harvest. Mean bunch fresh weight was negatively correlated with an index of root nematode infestation and positively correlated with the number of living roots. For the plant-crop and plant-crop plus ratoon yields, the yield increase due to combined use of fertilizer and hot-water treatment was larger than increases attained by individual measures. Thus combination of hot-water treatment and fertilizer had a synergistic effect on plantain fresh bunch yield, justifying introduction of both measures simultaneously.